A Widespread Early Mesozoic Remagnetization in South China. Issue 1 (19th January 2019) - Jiao, Wenjun; Li, Yong‐Xiang; Yang, Zhenyu; Liu, Jiarun
Abstract: The recent discovery of a possible Late Cambrian true polar wander (TPW) from the Jiangshan section in eastern South China has intrigued us to test this TPW in other continuous, well‐dated Upper Cambrian successions. We have conducted a detailed paleomagnetic study of a continuous Upper Cambrian succession in Wa'ergang, Hunan Province, middle South China, that contains well‐defined trilobite zones correlative with those of the Jiangshan section. Three remanence components were isolated from the Upper Cambrian limestone. The low‐ and intermediate‐temperature components represent a recent viscous magnetization and a Cretaceous remagnetization, respectively. The high‐temperature component passes fold tests, but its pole lies close to the Middle Triassic pole of South China, indicating a Middle Triassic remagnetization. Rock magnetic analyses and petrographic observations indicate that the high‐temperature component resides in small framboidal magnetite aggregates that were formed via alteration and replacement of pyrite and represents a chemical remagnetization. This Middle Triassic remagnetization and previously recognized Triassic remagnetization exhibit a younging trend from the east to the west of South China. The widespread Triassic remagnetization was likely associated with the Indosinian orogeny during which the scissor‐like suturing processes between the South and North China Blocks and the accompanying so‐called squeegeed orogenic fluids led to progressively westward younging remagnetization in South China. Although the new paleomagnetic results do not allow us to effectively test the Late Cambrian TPW due to the thorough remagnetization, these data provide important insights into understanding the Early Mesozoic remagnetization and associated geological processes. Key Points: A prefolding, Middle Triassic chemical remagnetization is recognized in the well‐dated Upper Cambrian succession in South China A younging trend of the Triassic remagnetization from the east to west is first identified in South China The remagnetization was likely related to orogenic fluids associated with the scissor‐like collision between South and North China Blocks